Penggunaan Metode AHP dalam pemilihan Jenis Promosi Kampus Berdasarkan Lokasi Sekolah - Indriaturrahmi Indriaturrahmi; Andris Faesal; Angan Febriana; M. Citra Satria (Journal of Computer System and Informatics (JoSYC), 2022)
Basically promotion is carried out to introduce goods or services to the consumer community so that they feel interested and interested in buying or using the products and services offered. As for the campus, promotion is carried out not only to introduce the campus environment, but also to maintain its existence in society. The problems encountered related to campus promotion include determining the type of campus promotion based on the area or school location which is still carried out randomly, so it is difficult to determine the right type of promotion based on the location of the promotion objective. The purpose of this research is to determine what type of campus promotion is best in each region based on the location of the school using the Analytical Hierarchy Process (AHP) calculation method. The results of this study indicate that the selection of criteria consists of two types, namely the criteria for school location and type of promotion and based on the results of campus management decisions and student historical data. The calculation results show that the average results for each area of ​​social media and partnership presentations are the highest with a value of 60%, and for visits to schools by 20%, and for the use of billboards by 20%.